Design and Construction of Batik Drawing Machine with an Arduino-based CNC System - Sitompul, Erwin; Ardanta Yoga, Raden Hilary; Galina, Mia (PROtek : Jurnal Ilmiah Teknik Elektro, 2024)
Technology continues to develop, especially in the world of manufacturing. Processes done manually by humans are replaced gradually by machines through automation. This paper proposes a batik drawing machine with Arduino-based computer numerical control (CNC). The intention is to reduce the production of small-sized batik products by eliminating the sketching process of the batik design on the fabric. Besides, the expertise in using canting, a pen-like tool, to apply the liquid wax on the fabric will not be required. A prototype of a batik drawing machine was designed and constructed using main components such as Arduino Mega 2560, NEMA17 HS4401 stepper motor, and RAMPS 1.4 controller board. The batik design data is to be prepared by using a graphic editor, computer-aided design (CAD), and computer-aided manufacturing (CAM) software. After several trials, the best setting for the canting temperature was found to be 112Â Â°C with a drawing speed of 25 steps/mm and a 3 mm distance between the cloth and the tip of the canting. Three batik designs with different difficulty levels were tested for fabric printing. The fabrics were colored to obtain the final results. The batik products with a diameter of up to 450 mm can be finished satisfactorily